Too “Big-Headed”, to Exit, a Massive Fetal Hydricephalus Causing Maternal Uterine Rupture. : Uterine Rupture After Delivery of Fetal Hydrocephalus - Jihwaprani, Muhammad Candragupta; Ismirahmadani , Tiara Dinar; Kurniawan, Hendro (Ahmad Dahlan Medical Journal, 2024)
Uterine rupture is an obstetric emergency, defined as a complete tear of all three layers of the uterus. It carries catastrophic maternal and fetal outcomes. While most commonly associated with previous cesarean deliveries or surgical obstetric-related procedures, it may very rarely be associated with abnormally high intrauterine pressure secondary to obstructed labor. Our center experienced a referred case of a spontaneous uterine rupture occurring after augmentation of labor and instrumental delivery of a hydrocephalic intrauterine fetal demise in an unbooked 29-year-old G4P3002 woman at 33 weeks’ gestation. She presented with acute hypotension and severe postpartum hemorrhage. Uterine rupture was diagnosed on clinical grounds. Early stabilization by maternal resuscitation and bleeding control was followed by an emergency total hysterectomy due to refractory hemorrhage. Our case depicted obstructed labor as a potential cause of uterine rupture and underpins the importance of routine antenatal care awareness which is still frequently overlooked in developing countries